(3QSGdI aj GdMQGQIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3bGd ehdGfG SCd ehdGfG YdGeI GdYUQ fLe GdedI hGdOjf Yf bhd GdTjN GdQFjS Cf GdMQGQI JaYd ai GdQWH ShGOkG hai VOg HjGVkG s
(3BNQgG (B:s
(3hai GdMeCI hGdWjf aEf GdZGdH Ydi WHjYJgG GdHjS ceG ai GdCMLGQ GdShO ai GdLHGd hZjQg agPG eG YfOi ai gPg GdeSFdI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKdGKhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs